REIMAGINATION OF OTHELLO AS OMKARA - Uday Sunil Adhagale, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Othello is one of the most celebrated tragedies by William Shakespeare set around the Ottoman Venetian War. Omkara (2006) is the transposition of “Othello” adheres to the landscape and culture of eastern Uttar Pradesh (UP). Critically acclaimed and nominated for eighteen Filmfare awards and won half of them.